Qualifying heritage through postcolonial moments (2018)
‘With the exhibition in the main building the aim was to show similarities as well as differences between the African enslaved workers and the Danish masters, and this was done by telling stories about the working and leisure life of both parties at the plantation.’1 Written jointly by most of the Danes involved in the Frederiksgave project, this quote informs us of the thoughts behind the exhibition set up in the newly reconstructed buildings. It shows how a dual figure of similarity and difference was used for structuring the exhibition at the Frederiksgave site. Moving on from the previous chapters’ exploration of the project design, architectural drawings, tools, materials and values, I now turn to the life of the ‘finished’ exhibition and plantation site of Frederiksgave.